E-cigarette environmental and fire/life safety risks in schools reported by secondary school teachers - Maryanne L. Fakeh Campbell; Andrew Sansone; Lauren N. Gonzalez; Kevin R. J. Schroth; Derek G. Shendell (BMC, 2020)
Abstract Background To identify if e-cigarette usage is an on-campus problem for secondary schools and evaluate initial school survey responses. More specifically, this survey can aid in identifying where students are seen using e-cigarettes, if smoke alarms have been newly inserted on school property, if smoke alarms have been tampered with to allow for vaping without detection; and, if any e-cigarette fires or explosions have occurred on school property. Methods This survey, disseminated to New Jersey secondary school teachers across seven sessions January-July 2019, resulted in 104 complete responses of 109 respondents. The survey was conducted after fire prevention, exit/egress, and life safety portions of "OSHA 10 Plus for General Industry" courses. Survey questions included number of times teachers observed students vaping and location where vaping in last 12 months, fire alarm installation and tampering, and fires or explosions and injuries from vaping/e-cigarette devices. Results Many (63%) respondents reported very or moderately common rates of vaping within their schools; however, three of four questions regarding school fire and smoke alarm use specifically to detect vaping had a majority of unsure/I don't know responses. Conclusion Results suggested concerns regarding student vaping and e-cigarette use inside and outside secondary schools. Improved school detection and response are warranted. Trial registration Not applicable.